δ11B of well-preserved brachiopod fossils coupled with geochemical modeling - Shelbie Legett (PANGAEA, 2020)
We present the δ11B of well-preserved brachiopod fossils coupled with geochemical modeling to examine how seawater boron responded to abrupt and dynamic climate changes in the Late Paleozoic. The Late Carboniferous, a time of major coal formation and glacio-eustatic sea level changes, is characterized by relatively stable brachiopod δ11B of 15-17 extperthousand, similar to values seen in modern brachiopods. Brachiopod δ11B dropped by ~5 extperthousand in the early Permian and then re-stabilized at a new value of 10 extperthousand within a few million years. Mass balance models of seawater δ11B reproduced the overall trends in our brachiopod data but failed to capture the large drop in δ11B in the early Permian. Published seawater 87Sr/86Sr and δ44/40Ca data based on brachiopod shells also shift to lower values in the early Permian, suggesting a common control on all three seawater isotope systems. The Permian terrestrial record of evaporites and eolian deposits suggests a prolonged reduced delivery of dissolved weathering products to the ocean, accounting for the change in seawater 87Sr/86Sr. This reduced weathering, in turn, led to increased atmospheric CO2 and lowered seawater pH, which may have significantly decreased major removal mechanisms for seawater calcium and boron leading to declines in both isotope systems. We propose that boron removal via coprecipitation in carbonates and adsorption onto clay minerals was significantly diminished due to a reduction in the availability of the borate aqueous species caused by lowered seawater pH.